G222(P) Admission hypothermia in extremely preterm neonates: a case control study. (May 2019) - Hart, L; Sinclair, C; Harris, C; Bhat, R; Greenough, A
Abstract : Aims: Admission hypothermia in infants born at less than 33 weeks of gestation has been associated with increased mortality and morbidity. 1 We investigated the effect of admission hypothermia on outcomes in extremely preterm infants (<28 weeks of gestation) admitted to our neonatal intensive care unit (NICU). Methods: This is a retrospective case control study from a single tertiary NICU. Badgernet was used to identify extremely preterm infants admitted between January 2016 to December 2017 who were hypothermic on admission (≤36.4°C). We identified gestational age and birth weight matched controls who were normothermic (≥36.5°C) on admission during the same period. Infants born at home and those with significant congenital abnormalities were excluded. Data were collected on admission temperature, mortality, time spent in each BAPM level of care (2011) 2 and the duration of ventilation and TPN requirement. We also compared morbidity: necrotising enterocolitis (NEC), retinopathy of prematurity (ROP), intra-ventricular haemorrhage (IVH) and bronchopulmonary dysplasia (BPD) at 36 weeks. Differences between groups were analysed using SPSS with Mann Whitney U or Chi Square test as appropriate. Results: Twenty-six infants with hypothermia were compared to 26 matched controls. The groups were well matched with no significant differences in median gestational age or birth weight. Infants with hypothermia required a longer duration of level one intensive care (median 47 days, range 1–129 versus median 23 days, range 1–79, p=0.003), were ventilated for longer (median 35 days, range 1–129 versus median 18 days, range 1–77, p=0.009) and required TPN for longer (median 37, range 0–139 versus median 16, range 0–66, p=0.004). There was no significant differences in the Apgar score at five minutes, mortality, BPD at 36 weeks, NEC, ROP requiring treatment, or grade four IVH between the groups. Conclusion: Our data demonstrate that admission hypothermia is associated with longer intensive care stay in infants born extremely prematurely and further justifies the use of admission temperature as an important target for best clinical practice. References: Laptook A, et al. Pediatrics 2018;192:e53–9. https://www.bapm.org/sites/default/files/files/CatsofcarereportAug11.pdf